Application of the Apriori Algorithm to Analyze the Correlation of Underage Marriage Factors - Rizki Tri Ipanda; A M H Pardede; Melda Pita Uli Sitompul (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
This study aims to analyze the correlation between various factors contributing to underage marriage in Kota Binjai. The primary variables influencing underage marriage include economic, social, cultural, parental, and educational factors. These five variables are considered significant in the prevalence of underage marriage within the Kota Binjai community. The methodology employed involves data mining techniques using the Apriori algorithm to identify the most frequently occurring data correlations. The analysis reveals that the best rule with 2 itemsets has a support of 42.7% and a confidence of 69.6%, while the best rule with 3 itemsets has a support of 26.7% and a confidence of 71.4%. For 4 itemsets, the support is 12% with a confidence of 50%. These findings indicate that economic factors are the most frequently appearing and consistently influential in the decision of Kota Binjai residents to engage in underage marriage, both independently and in combination with social, cultural, and parental influence factors